Comparative Genomic Analysis of Type VII Secretion System in Streptococcus agalactiae Indicates Its Possible Sequence Type-Dependent Diversity - Zhou, Kaixin; Xie, Lianyan; Xu, Xiaogang; Sun, Jingyong (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus agalactiae causes sepsis and meningitis in neonates, presenting substantial clinical challenges. Type VII secretion system (T7SS), an important secretion system identified in Mycobacterium sp. and Gram-positive bacteria, was recently characterized in S. agalactiae and considered to contribute to its virulence and pathogenesis. In the present study, 128 complete genomic sequences of S. agalactiae were retrieved from GenBank to build a public dataset, and their sequences, capsular types, and clonal complexes were determined. Polymerase chain reaction (PCR) screening and genomic sequencing were conducted in an additional clinical dataset. STs and capsular types were determined using PCR. Eleven different types of T7SS were detected with similarities in gene order but differences in gene content. Strains with incomplete T7SS or lack of T7SS were also identified. Deletion, insertion, and segmentation of T7SS might be related to insertion sequences. The genetic environment of T7SS in S. agalactiae was also investigated and different patterns were identified downstream the T7SS, which were related to the diversity of T7SS putative effectors. The T7SS demonstrated possible sequence type (ST)-dependent diversity in both datasets. This work elucidated detailed genetic characteristics of T7SS and its genetic environment in S. agalactiae and further identified its possible ST-dependent diversity, which gave a clue of its mode of transmission. Further investigations are required to elucidate the underlying mechanisms and its functions.